Impact of Age Management on Sustainability in Czech Organisations - Hana Urbancová (Sustainability, 2020)
Age management is becoming an increasingly important part of strategic human resources management practices and can ultimately lead to a competitive advantage. Research results confirmed that a strategic focus on the efficient use of all age categories of employees yields retention, the successful achievement of organisation goals, development, and, ultimately, a competitive advantage. The aim of this article is to identify and evaluate approaches to age management practices in organisations in 1271 organisations in the Czech Republic. Quantitative research was carried out in selected organisations operating over a three-year period. Data was gathered from these organisations and evaluated using descriptive and multidimensional statistics. The results show that those organisations focusing on the application of age management practices achieved a competitive advantage regardless of size or sector of the organisation. Statistical analysis (χ2 test, Cramer’s V, factor analysis) on survey data shows that many of these organisations achieved significant perceived benefits from the application of age management. The approach to age management application varies in organisations depending on whether it is an internal branding of an employer or response to a crisis. Organisations either use of best practices to implement age management or it is a carefully planned process in advance. Follow-up research can focus on the use of age management in crisis management or employer branding. This study is a non-experimental quantitative correlation analysis utilising longitudinal empirical data.